DEVELOPMENT POSSIBILITIES OF THE GREEN ECONOMY IN LATVIA (EXAMPLE OF REZEKNE MUNICIPALITY) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Preserving natural capital is important topic in 21st century in order to ensure prosperity by sustaining qualitative ecosystem services that are both - non-material and material benefits provided by nature. As research outlines, green economy is based on three pillars of sustainable development - social, economic and environmental. It was concluded, that the main principles of the green economy are sustainable development, which stimulates economic growth, reduces poverty, while placing natural capital as a major asset; development adapted to the interests and opportunities of each country, regions and local areas ensuring participation of the population, social inclusion; promotion of green industries (renewable energy, waste management, sustainable agriculture); efficient use of natural resources. Research paper analyses the current situation and future potential of Latvia in the implementation of the green economy, taking as the example evaluation of the situation in the Rezekne Municipality. Research methods such as logical constructive method, document analysis, and interviews were used to gather, analyse and reflect information which was then used to create evaluation model that was used in the focus group to assess weaknesses and potential of Rezekne Municipality, for example, potential in the production of gas from waste. Also important is education of society and their involvement in non-governmental organizations, and the development of the greener way of thinking, where there are noticeable weaknesses. It is possible to take direct examples from other countries (case studies from Finland, France, Lithuania, and Great Britain) that already have experience and real results.